The Speed of Land Use Changes in The Region of Depok City - Fatin Vidya Utami; Mulyo Hendarto (Economics Development Analysis Journal, 2020)
This study aims to analyze the conditions of distribution location, the speed, the development direction and the influence of the accessibility, public facilities, land characteristics (topography), land value and population growth factors on the speed of land use change in the core and periphery regions of Depok City in 2013-2017. The methods used are spatial overlay analysis, the speed of land use change, gravity, scalogram and descriptive analysis. The results showed that the distribution locations of land use change in the coreregion were spread in the areas that close to the central government of Depok City and has stability with the South Jakarta City. Meanwhile, in the periphery region, it spread in areas that have a large proportion of agricultural land, correlated with the closest cities/ regencies and traversed by the good accessibilities. The speed of land use change in the periphery regions of Depok City occurs faster than the core region, with the direction of development towards the west of Depok City. In addition, there were also found that the factors influenced the speed of land use change in the core region is land value factor. Meanwhile, in the periphery region, it was influenced by different factors in each of the development area, with influential factors such as accessibility, public facilities, land value and population growth factors. Meanwhile, landcharacteristics factor (topography) does not affect to the speed of land use change in the core and periphery regions of Depok City in 2013-2017.